(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
The cost-effective design could be done in many ways, such as by reducing the cost of energy lost, reducing manufacturing cost, reducing annual maintenance costs, etc. 3-phase induction motors are extensively used as the most effective machine in the industry because they are reliable and economical. The cost-effective design of this motor is a great challenge for engineers. The Induction motor design is a non-linear and multivariable optimization problem. So, the entire problem depends on the selection of variables and constraints. Lesser number of constraints leads the poor performance, and on the other hand, improper selection of bounds of the variables gives the odd dimension of the motor. The proposed work deals with the design and optimization of the cost of production subject to various constraints with a selected number of variables. A gravitational search algorithm (GSA) is used to get the desired optimal results, and based on that, the performance indices and cost of production are calculated. The proposed algorithm is used to find the optimal cost for two motors, and finally, the output is compared with the particle swarm optimization (PSO) to validate the results. The production of GSA shows more acceptable values of design parameters and performance indices, which are projected in the result section and discussed in the conclusion section.